2017
DOI: 10.1136/archdischild-2017-313418
|View full text |Cite
|
Sign up to set email alerts
|

Nasal injury in preterm infants receiving non-invasive respiratory support: a systematic review

Abstract: Nasal injury is common in preterm infants born <30 weeks' gestational age receiving CPAP via binasal prongs. Larger randomised trials are required to fully evaluate strategies to reduce nasal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 49 publications
2
101
0
4
Order By: Relevance
“…A similar meta-analysis (only for nasal trauma) performed in a recent systematic review 9. A borderline reduction (RR (95% CI) 0.80 (0.64 to 1.00); P=0.05) in the rate of nasal injury is seen in infants receiving mask NCPAP.…”
Section: Summary Of Evidencementioning
confidence: 82%
“…A similar meta-analysis (only for nasal trauma) performed in a recent systematic review 9. A borderline reduction (RR (95% CI) 0.80 (0.64 to 1.00); P=0.05) in the rate of nasal injury is seen in infants receiving mask NCPAP.…”
Section: Summary Of Evidencementioning
confidence: 82%
“…More specifically, a meta‐study by Imbulana et al. () found that between 20 and 100% of premature infants sustained a nasal injury attributable to binasal prong CPAP. Furthermore, the use of mechanical ventilation was found to increase infections among neonates (Tan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, nCPAP delivery systems are associated with significant risk of nasal trauma [10, 11]. Imbulana et al [11] assessed the incidence of and risk factors for nasal injury in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…Imbulana et al [11] assessed the incidence of and risk factors for nasal injury in preterm infants. In their systematic review including 45 trials, the reported incidence of nasal injury in preterm infants receiving nCPAP ranged from 20 to 100%.…”
Section: Introductionmentioning
confidence: 99%